Bullous pilomatrixoma. - Garofalo, S.; Guanà, R.; Scottoni, F.; Cortese, M.G.; Cerrina, A.; Linari, A.; Carli, D.; Ferrero, G.B.; Gennari, F. (European Journal of Pediatric Dermatology, 2020)
Pilomatrixoma is a benign tumor of the skin. It is a very common childhood tumor arising from the matrix cells of hair follicles (4). Most common localizations are head, neck, and upper limbs. Common features include the tent sign, i.e. uneven facets and edges at stretching the skin above the lesion and teeter-totter sign, namely tilt of the lesion at alternating pressure on the sides. Pilomatrixomas usually appear as solitary nodules. However, multiple lesions are reported in patients affected by myotonic dystrophy, familial adenomatous polyposis, Gardner syndrome, Turner syndrome etc. (4). […]